Experiences of online learning during COVID-19 pandemic lockdown period: a cross-sectional survey among the college students in India - Saraf, Nikita; Doss, Prakash S.; Tahakik, Sanskruti; Reddy, Kowshik B.; Rangasamy, Arun; Swamy, Sheetal; Bharti, Avinash Kumar; Bhandari, Tanushree; Singh, Jagan Deep; Ruati, Lalrem (International Journal Of Community Medicine And Public Health, 2021)
Background: The COVID-19 pandemic forced educational institutions across the world to shut down their campuses adhering to the lockdown protocols. As a result, higher educational institutions seek to deliver education through online platforms. This sudden shift created a huge impact on students learning capabilities. Methods: We conducted an online cross-sectional survey to assess the college student’s perspective about the online learning and also the most common problems faced in this online learning. A 17 item Google form questionnaire was structured by the authors. We received responses 1834 students from different higher educational institutions across India. Results: The results revealed that 71.7% of students rated the pandemic online learning below moderate on a 5-point scale. The students felt that they learn better in offline classrooms (78.9%) and reported few technical issues which hinder their learning capacity. The students appreciated the flexibility of learning from home, availability of more personal space, accessibility of abundant online learning resources, and wide range of online learning platforms in this online learning. However, most of the students felt that online learning is stressful and affects their mental health in particular. Conclusions: The study reveals the importance of online education in the near future. As we scale up to the future, this survey findings warrant a prompt action to improve digital infrastructure to resolve the technical issues, reduce cost involvement, well-structured training to improve pedagogical skills and technical skills of the faculty members.